2023
DOI: 10.18632/aging.204484
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the gut microbiome changes with aging in a novel Alzheimer’s disease rat model

Abstract: Alzheimer's disease (AD) is one of the most devastating diseases currently in the world with no effective treatments. There is increasing evidence that the gut microbiome plays a role in AD. Here we set out to study the age-related changes in the microbiome of the Tgf344-AD rats. We performed 16S ribosomal RNA sequencing on the fecal samples of male rats at 14 and 20 months of age. We found the Tgf344-AD rats to have decreased microbial diversity compared to controls at 14 months of age and this was found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
4
8
1
Order By: Relevance
“…We detected several bacterial taxa changes due to Diet at 1 week and 18 weeks but surprisingly not at 57 weeks. In our current study, we found alpha diversity metrics decreased with age, similar to our earlier published report where we saw alpha diversity decrease with age in Fischer344 rats (Nagarajan et al., 2023 ). However, others investigating the mouse microbiome did not report any changes in diversity with age (Binyamin et al., 2020 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We detected several bacterial taxa changes due to Diet at 1 week and 18 weeks but surprisingly not at 57 weeks. In our current study, we found alpha diversity metrics decreased with age, similar to our earlier published report where we saw alpha diversity decrease with age in Fischer344 rats (Nagarajan et al., 2023 ). However, others investigating the mouse microbiome did not report any changes in diversity with age (Binyamin et al., 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…This is further evidence that the gut microbiota changes significantly with age. The F/B ratio did not differ with age in our current study or our previous study with F344 rats (Nagarajan et al, 2023). The work of Binyamin and colleagues conflicts with ours, however, as they have reported an increased F/B ratio with advanced age (Binyamin et al, 2020).…”
Section: Discussioncontrasting
confidence: 78%
“…Studies in recent years have shown that bacteria produce a number of compounds that cause the development of systemic inflammatory responses that impair the blood–brain barrier (BBB), exacerbating neuroinflammation and ultimately neurodegeneration [ 79 , 80 , 81 ]. The microbiota produces a number of neuromediators such as serotonin, kynurenine, melatonin, GABA (gamma-aminobutyric acid), tryptophan, catecholamines, histamine and acetylcholine [ 82 , 83 ].…”
Section: Oral Microbiome In Systemic Diseasesmentioning
confidence: 99%
“…The development of Alzheimer’s disease [ 69 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ] and the mechanisms through which the microbiome can contribute to the progression of Alzheimer’s disease have been investigated [ 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 ]. Numerous studies are also available regarding treatments with probiotics […”
Section: Discussionmentioning
confidence: 99%